The impact of the Rht‐B1b, Rht‐D1b, and Rht‐8 wheat semi‐dwarfing genes on flour milling, baking, and micronutrients. Issue 6 (24th August 2018) - Jobson, Emma M.; Martin, John M.; Schneider, Tavin M.; Giroux, Michael J.
Abstract: Background and objectives: The introduction of the semi‐dwarfing Reduced Height ( Rht ) genes in wheat led to dramatic yield increases. The two most common forms of the gene, Rht‐B1b and Rht‐D1b have been widely incorporated into wheat varieties. However, despite their agronomic benefits and prevalence in modern wheat cultivars, much less is known regarding their impact on end‐use quality and nutrition. For this study, we compared near‐isogenic lines (NILs) carrying either Rht‐B1b, Rht‐D1b, Rht‐8 or no semi‐dwarfing alleles. Findings: Our agronomic results agreed with previous studies; we observed a 25% height reduction, 13% yield increase, and a 2% decrease in grain protein content in the semi‐dwarf NILs. However, despite the decreased protein content, the Rht‐B1b/Rht‐D1b NILs had increased bake mixing time (33%), but reduced loaf volume (7%). We also observed that although the semi‐dwarfing alleles decreased kernel weight by 15%, they were associated with a 2% increase in flour yield. Flours prepared from the semi‐dwarf NILs had decreased Zinc, Iron, and Manganese while having increased levels of Potassium and Calcium. Conclusions: These findings demonstrate that while Rht‐B1b/Rht‐D1b negatively impact kernel size and protein content they positively impact flour yield and dough mixing strength. Significance and novelty: The most common wheat semi‐dwarf alleles decrease kernel size, protein, and micronutrient content while increasing flour yield.